(untitled) (Tanzania Medical Journal, 2021)
Background Choroidal melanoma presents the most common type of uveal melanoma commonly diagnosed as a local tumor with about 2% already spread to distant organs necessitating early diagnosis and intervention. The case is presented to show the challenge of managing metastatic choroidal melanoma in a Tanzanian setting. Case report A 45 years old male presented at The Comprehensive Community Rehabilitation in Tanzania (CCBRT) hospital with four weeks’ history of acute painful progressing right eye visual loss associated with headache, nausea and vomiting. On examination the eye had a dome shaped retinochoroidal tumor on the inferior extending to the macula associated with shallow retinal detachment. Ultrasonography showed an acoustically silent zone within the tumor, choroidal excavation with some orbital shadowing whereas orbital CT scan revealed a hyper dense lesion. Systemic evaluation for metastasis gave imaging evidence of spread to the liver, lungs and kidneys. Tissue histology of the enucleated eye confirmed epithelioid melanocytic tumor cells. The patient was counselled on the prognosis, referred for palliative care but absconded and died four months later. Conclusion Management of metastatic choroidal melanomas is clinically challenging owing to faster growth with poor prognosis even in good hands. Early diagnosis and treatment is important as the final prognosis depends largely on the size, location and extent of metastasis. Enucleation is the final treatment modality for most of the large tumors though it has limited a value in the metastatic type, which ends up with palliative care or death.